ANTIMICROBIAL DRUG MISUSE IN THE EASTERN DEMOCRATIC REPUBLIC OF THE CONGO A CROSS-SECTIONAL STUDY: FACTORS INFLUENCING THE EMERGENCE OF ANTIMICROBIAL RESISTANCE - MORISHO, LAMBERT; AMISI , BAMAVU; MANIKASSE , GAKNE; NYEMBO , BANZA; MUNYUKU , ISOKELO; MUGANDA , CIRIMWAMI; BATUVANWA , WITANDAY; MWENGE , MUNGUAKONKWA; MORISHO , KIPINDULA (Student’s Journal of Health Research Africa, 2024)
Background Antimicrobial resistance is a major global public health challenge. In sub-Saharan Africa, Plasmodium resistance to new molecules on the market continues unabated. This increase in resistance is mostly due to unhealthy community practices, and also to microbial control methods that are ineffective because of our health policies. This study aimed to analyze factors involved in the emergence of antimicrobial resistance in ancient Kivu, in the eastern part of the Democratic Republic of Congo (DRC). Materials and methods A cross-sectional study was carried out from November 2023 to February 2024 in two cities east of the Democratic Republic of the Congo, surveying pharmacies using a standardized questionnaire. We focused on four elements within the pharmacies: the nature of the provider, the way medicines are sold (consumption), the location of the pharmacies, and the nature of drugs. Results Our study included 98 (56.9%) pharmacies, 66.3% (65/98) of which were located in peripheral areas with most of the untrained providers (91.7%; 11/12; p = 0.006) and in all pharmacies, 81% (47/58; p < 0.001) of their sales were based on patients’ wishes. Nursing sales are 76.9% (20/26; PR: 1.9; 95% CI: 0.5-7.4; p = 0.009) undocumented among qualified staff involved in pharmacy sales. Conclusions The risk factors for developing antimicrobial resistance in these two cities in eastern DRC are related to undocumented drug sales and qualified providers in pharmacies. This requires a high level of awareness among those involved in the sale of medicines and those who receive them. Recommendation Our proposal is for strict protection of antimicrobial resources through regulation of their sale in the region.